The Pengaruh Brand Image terhadap Minat Beli Wisatawan Domestik di The Oberoi Beach Resort, Bali - Dewi, Ni Gusti Ayu Made Yuliana; Jata, I Wayan; Witarsana, I Gusti Agung Gede; Diwyarthi, Ni Desak Made Santi (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2025)
This research was prompt by the number of domestic visits at The Oberoi Beach Resort Bali which had low visits compared to visits by foreign market shares. This study aims to analyse the impact of brand image on the buying interest of domestic tourists and the extent to which brand image has a significant influence on buying interest at The Oberoi Beach Resort, Bali. The data in this study was collected by questionnaire distribution techniques that use the Likert scale as a measuring tool, sampling was carried out based on non-probability sampling techniques, samples were purposively selected. The sample used amounted to 100 respondents from domestic tourists. The data collected was carried out quantitative analysis using SPSS software version 25 for Windows. This analytical approach involves testing rules for classical assumption testing, simple linear regression, t-test analysis and determination analysis. The results showed that brand image had a significant effect on the buying interest of domestic tourists at The Oberoi Beach Resort, Bali. With a tcount (12.623) > ttable (1.98447) and a coefficient of determination test value (R2) with a strong influence category with a percentage of 61.9%. In conclusion, it is important to increase a positive brand image to increase the buying interest of domestic tourists at The Oberoi Beach Resort, Bali. The practical implication of this research highlights the need for targeted branding strategies that resonate with domestic tourists by emphasizing local cultural elements, offering personalized domestic packages, and increasing brand familiarity through localized marketing efforts.